Estudos sobre a inclusão da correlação eletrônica do alvo no espalhamento elástico elétron-molécula e sobre a ionização molecular por impacto de elétrons - Martins, Maria das Graças Reis (2003)
In this work we present two contributions to the electron-molecule collision theory. Firstly, we present a new theoretical procedure to introduce the target electronic correlation in the elastic electron-molecule scattering. By our procedure we use the configuration interaction (CI) wave function of the target to determine the scattering potential. Static, exchange and polarization contributions are explicitly obtained in terms of the molecular spin-orbitals thus allowing, in principle, that an arbitrary number of configuration state functions (CSF) be used in the determination of the differential cross sections (DCS). We have focused our studies on the elastic electron-molecule scattering considering N2, CO, H2O, H2 and CH4 molecules and the 0.5 - 30 eV energy range. For the first four molecules the DCS were obtained using the Schwinger variational iterative method (SVIM). For CH4 and also H2 we have used the method of continued fractions (MCF). Our results were compared with experimental data and theoretical results using different methods, all of them based on Hartree-Fock (HF) wave functions. Secondly, we present a study of molecular ionization by electron impact. We consider the H2 molecule and the process (e, 2e) using the symmetric coplanar and asymmetric coplanar geometries. For this study we have used a code based on the MCF. In this case we have developed a new version of the code in order to make it capable of determining the quantities (reactance K matrices and ejected-electron continuum wave functions) needed in ionization studies, since the applicability of the existing previous versions was restricted to electron-molecule scattering and molecular photoionization calculations. Triply differential cross sections (TDCS) were calculated and compared to experimental and/or theoretical data available in the literature.